Books and ebooks in an academic library - Wells, David; Sallenbach, Anita (Australian Library and Information Association Ltd, 2015)
This article tests ALIA's statement that ‘library print and ebook collections will establish a 50:50 equilibrium by 2020’ against the experience and likely trajectory of Curtin University Library. It identifies features of the higher education landscape that have led to the development of epreferred strategies, outlines current collection principles, and describes the current state of the Library's holdings. Looking ahead, the article charts the likely impact of the current collection development framework over the next six years, considering questions relating to budget, use of space, client experience and treatment of the legacy print collection.